Strategi Nation Branding Thailand melalui Kampanye "Go Thai Be Free" tahun 2013-2019 - Angkat, Fransiska Irmawati; Suwecawangsa, Adi Putra; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
LGBT tourism or Pink Tourism, is one of the fastest growing tourism fields in Thailand. Known as a "Gay Friendly Country", "Gay Paradise", makes Thailand one of the favorite tourist destinations for international LGBT tourists. Having a negative image due to the existence of sex tourism, especially when viewed from the history of LGBT Tourism development, has made Thailand attemp to create positive branding in the field of LGBT tourism. In order to achieve this branding, the Tourism Authority of Thailand established the tourism campaign "Go Thai Be Free" which was officially launched in 2013. In this research the authors used a type of qualitative research using the concepts of nation branding and pink tourism. Through this campaign Thailand used various strategies to carry out positive branding through tourism promotion. The strategies carried out through establishing a branding identity through the "Go Thai Be Free" campaign, creating official social media, establishing communication with international LGBT tourists through the official website and Thailand LGBTQ+ Travel Symposium, celebrating various LGBT festivals, and appoint a brand ambassadors to carry out broader and more attractive promotions. All of these strategies are to promote LGBT tourism that is friendly to the international LGBT community. Keywords : go thai be free, LGBT , nation branding, pink tourism, Thailand